Public perception towards government procurement system : evidence from the Eastern Region of Malaysia / Wan Mohammad Taufik Wan Abdullah ... [et al.] - Wan Abdullah, Wan Mohammad Taufik; Deris, Mohmad Sakarnor; Mohd Saad, Noriza; Haji Mohamad, Marziana; Tarmidi, Mahlindayu (Universiti Teknologi MARA, Shah Alam, 2011)
In the Malaysia public sector, it has to be acknowledged that there have been tremendous improvements in financial management especially in the last few years. However, despite numerous reminders on the importance of good financial management and proper record keeping, problems still continue to occur year after year and this is clearly evident by the Auditor-General Report, which highlights many incidents of financial mismanagement. Most of the incidents highlighted in the Auditor-General Report are due to non-compliance to the existing laws, regulations and financial procedures or simply due to the complete lack of integrity and accountability on the part of the financial managers. Government procurement is a business process within a political system of a government which is largely decentralized and subject to regulations and requirement of several financial provisions. This project aims to explore the public’s perception toward the government procurement system. The results of this study indicated that the perceptions of the public is satisfactory towards the Malaysia government procurement system since there are still loopholes within the existing process and procedures which allow opportunity for corruption to occur.